Time in world history - Stearns, Peter N., author.
1 online resource
Keywords: "In this book, Peter Stearns presents the fascinating concept of time through a global historical lens. Covering both calendrical time and clock time, the volume shows how significant changes in conceptions of time are in world history, as they translate many key historical developments from religion to industrialization, into daily experience. The book explores why and how early societies became interested in measuring time as well as explaining the causes and ongoing consequences of the modern sense of time. The author compares different societies and cultures in their attitudes and approaches to time and describes the role of globalization in its development. The volume offers many examples and illustrations to aid readers in their understanding of the advantages and disadvantages of various constructions of time, both in the past and among different groups of people today. Time in World History will be of interest to students of world history and sociology, introducing readers to historical forces that continue to shape their lives quite directly"--